Single donor electronics and quantum functionalities with advanced CMOS technology. (12th February 2016) - Jehl, Xavier; Niquet, Yann-Michel; Sanquer, Marc
Abstract: Recent progresses in quantum dots technology allow fundamental studies of single donors in various semiconductor nanostructures. For the prospect of applications figures of merits such as scalability, tunability, and operation at relatively large temperature are of prime importance. Beyond the case of actual dopant atoms in a host crystal, similar arguments hold for small enough quantum dots which behave as artificial atoms, for instance for single spin control and manipulation. In this context, this experimental review focuses on the silicon-on-insulator devices produced within microelectronics facilities with only very minor modifications to the current industrial CMOS process and tools. This is required for scalability and enabled by shallow trench or mesa isolation. It also paves the way for real integration with conventional circuits, as illustrated by a nanoscale device coupled to a CMOS circuit producing a radio-frequency drive on-chip. At the device level we emphasize the central role of electrostatics in etched silicon nanowire transistors, which allows to understand the characteristics in the full range from zero to room temperature.